Stripes [videorecording (Blu-Ray)] - Reitman, Ivan; Blum, Len; Goldberg, Danny, 1950-; Murray, Bill, 1950 September 21-; Ramis, Harold; Oates, Warren, 1928-1982; Soles, P. J.; Candy, John (Columbia TriStar Home Entertainment, 2012)
When John Winger loses his job, his car, his apartment, and his girlfriend, all in one day, he decides he only has one option: volunteer for Uncle Sam. He talks his friend Russell into enlisting with him. Where else, they figure, can they help save the world for democracy and meet girls!